Understand Curriculum History Culture Islam: SKL, KI, And KD That Can Enlighten Generation Young - Susanti, Weti; Vanessa, Anadya Diva; Anas, Khairul; Febrianti, Anisa; Rusydi, Khairul (Institut Agama Islam Sumatera Barat, 2024)
The subject of Islamic Cultural History plays an important role in forming a young generation with broad insight, noble character and love for the country. The well-structured Islamic Cultural History Curriculum provides a guide for teachers and students in understanding Islamic history and culture comprehensively. The aim of this research is the Graduate Competency Standards, Core Competencies and Basic Competencies in the History of Islamic Culture subject, a description of the abilities that must be achieved by students after completing education so as to enlighten students. The type of research used is literature. The data collection technique was carried out through library research, namely by collecting several articles from journals and books related to the Islamic cultural history curriculum related to SKL, KD and KI. The research results are a more in-depth analysis of KI and KD SKI shows several advantages as follows: 1) Protects the continuity of Islamic values: SKI helps instill Islamic values ​​in the younger generation through understanding Islamic history and culture 2) Increases insight and knowledge: SKI provides students with a broad insight into Islamic history and culture, helping them to understand the world around them better, 3) Develops critical thinking skills: SKI encourages students to analyze information critically and form their own opinions about Islamic history and culture, 4) Increasing tolerance and respect for differences: SKI helps students to understand and appreciate cultural and religious diversity, and increases their tolerance for differences. 5) Preparing students for the future: SKI equips students by helping the younger generation to understand Islamic history and culture better.